Factors Affecting Switching Intention from Cash on Delivery to E-Payment Services in C2C E-Commerce Transactions: COVID-19, Transaction, and Technology Perspectives - Betty Purwandari; Syahrul Alam Suriazdin; Achmad Nizar Hidayanto; Suryana Setiawan; Kongkiti Phusavat; Mutia Maulida (Emerging Science Journal, 2022)
During the COVID-19 pandemic, the application of e-payment has rapidly increased. However, e-payment has not been able to achieve a trustworthy level in e-commerce transactions. Thus, cash payment methods with Cash On Delivery (COD) services still dominate C2C e-commerce payment transactions in Indonesia. This study aims to investigate factors that affect users' switching intentions from COD to e-payment services. The research model was adopted by using the Push-Pull-Mooring framework, integrating perceived COVID-19 risk, technology acceptance, and transaction effort. Empirical research was conducted using data from 546 COD and e-payment users in Indonesia, with Structural Equation Modelling (SEM) being used to validate the model and analyze the hypotheses. The results indicate that switching intention from COD to e-payment is significantly influenced by pull factors in e-payment, which are economic benefits, performance expectancy, effort expectancy, and critical mass. There are also two mooring factors that significantly influence the switching intention from COD to e-payment, which are trust and perceived security and privacy. This study makes a significant contribution to the literature in terms of validating a theoretical framework that emphasizes factors that influence user switching intentions from COD to e-payment in the context of the COVID-19 pandemic. This research can be a reference for Indonesian payment system regulators and e-payment service providers in formulating regulations and strategies to accelerate the spread of digital transactions in Indonesia. Doi: 10.28991/esj-2022-SPER-010 Full Text: PDF